2015
DOI: 10.2196/medinform.5215
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes From Health Information Exchange: Systematic Review and Future Research Needs

Abstract: BackgroundHealth information exchange (HIE), the electronic sharing of clinical information across the boundaries of health care organizations, has been promoted to improve the efficiency, cost-effectiveness, quality, and safety of health care delivery.ObjectiveTo systematically review the available research on HIE outcomes and analyze future research needs.MethodsData sources included citations from selected databases from January 1990 to February 2015. We included English-language studies of HIE in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 50 publications
2
105
0
Order By: Relevance
“…While metric lists by organizations like the ONC 31 may not be the last word on measurement, such a compendium provides a starting point for existing approaches already in use. Already there are calls for greater attentiveness to designs, levels of measurement, and conceptual frameworks for outcome evaluations, 21,26 but our findings suggest the research and evaluation community can be more attentive to the glaring need for greater conceptual clarity about HIE in general. Our interviewees' experiences differed on multiple dimensions: state and local; community and enterprise; large and small; with and with academic participation; and with significant public funding and without.…”
Section: Data Qualitymentioning
confidence: 82%
See 1 more Smart Citation
“…While metric lists by organizations like the ONC 31 may not be the last word on measurement, such a compendium provides a starting point for existing approaches already in use. Already there are calls for greater attentiveness to designs, levels of measurement, and conceptual frameworks for outcome evaluations, 21,26 but our findings suggest the research and evaluation community can be more attentive to the glaring need for greater conceptual clarity about HIE in general. Our interviewees' experiences differed on multiple dimensions: state and local; community and enterprise; large and small; with and with academic participation; and with significant public funding and without.…”
Section: Data Qualitymentioning
confidence: 82%
“…13,14,15,16 More recently, research has begun to compare multiple HIEs within or across states to examine process and outcomes. 17,18 However, recent systematic reviews of the literature have been fairly critical, concluding that the existing evidence base for HIE as an effective intervention to change utilization, cost, and quality is insufficient, 19,20,21 and is falling short of expectations around the ability for data stored in HIEs to facilitate population level data.…”
Section: Introductionmentioning
confidence: 99%
“…Another important result of this work was the measurement of data quality metrics to gauge the impact of the eHealth-Interop platform in informational continuity of care, since impact of HIE are yet inadequately studied [44,45].…”
Section: Principal Resultsmentioning
confidence: 99%
“…Evidence about the benefits of HIE are encouraging [3]. Studies on HIE outcomes have reported modest to moderate reductions in duplicate laboratory and radiology testing [4][5][6], better identification of medication discrepancies and improved medication reconciliation [7].…”
Section: Introductionmentioning
confidence: 99%